2004
DOI: 10.1007/s11745-004-1194-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triacylglycerol structure on absorption and metabolism of isotope‐labeled palmitic and linoleic acids by humans

Abstract: The effect of dietary TAG structure and fatty acid acyl TAG position on palmitic and linoleic acid metabolism was investigated in four middle-aged male subjects. The study design consisted of feeding diets containing 61 g/d of native lard (NL) or randomized lard (RL) for 28 d. Subjects then received an oral dose of either 1,3-tetradeuteriopalmitoyl-2-dideuteriolinoleoyl-rac-glycerol or a mixture of 1,3-dideuteriolinoleoyl-2-tetradeuteriopalmitoyl-rac-glycerol and 1,3-hexadeuteriopalmitoyl-2-tetradeuteriolinole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…This is in conflict with some [12,13,23,27] but not all [10,28] earlier investigations using randomised SFA-rich fats. Our results are in line with those of Emken et al [29], who, using isotope-labeled TAGs, found that the other common SFA, palmitic acid, also undergoes substantial isomerisation after absorption, whereas the position is conserved with polyunsaturated linoleic acid. The anticipated increased fecal stearic acid losses from the sn-2 position [10,30] can be excluded as only marginal amounts were found in the feces [14].…”
Section: Discussionsupporting
confidence: 93%
“…This is in conflict with some [12,13,23,27] but not all [10,28] earlier investigations using randomised SFA-rich fats. Our results are in line with those of Emken et al [29], who, using isotope-labeled TAGs, found that the other common SFA, palmitic acid, also undergoes substantial isomerisation after absorption, whereas the position is conserved with polyunsaturated linoleic acid. The anticipated increased fecal stearic acid losses from the sn-2 position [10,30] can be excluded as only marginal amounts were found in the feces [14].…”
Section: Discussionsupporting
confidence: 93%
“…However, we have also to take into account that myristic acid is mainly in the sn-2 position in dairy TAG of the butterfat diet, whereas it is equally distributed in the 3 positions in the synthetic saturated TAG of the two other saturated fat diets (saturates and trimyristin diets) [37]. It has been suggested that fatty acids in the sn-2 position are better absorbed in enterocytes [38], but there are still controversies about the real physiological impact of fatty acids when located in the sn-2 position [39,40]. In our study, when analyzing the effect of the 3 diets containing 10-12 mol% myristic acid (butterfat, saturates and trimyristin), myristic acid was found significantly higher in adipose tissue of the rats fed the butterfat diet ( Table 3), suggesting that myristic acid in sn-2 position is indeed better absorbed or better stored.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusion from the data shown for percent conversion would be that diet did not have an Fig. 8 Effect of triglyceride acyl position on conversion of 2 H-18:2n-6 to 2 H-20:4n-6 in male subjects pre-fed native and randomized lard diets 16) .…”
Section: Human Studies Using Isotope Labeled Fatty Acids: Answered Anmentioning
confidence: 99%